Nonlinear oscillator of an artificial bone. Issue 3 (December 2019) - Wang, Qingli; Shi, Xiangyang
Artificial bone mimicking its living partner has porous structure and should have same fractal dimensions with the bone. This paper studies the transverse vibration of the artificial bones which is considered as a porous plate. The result is helpful for designing artificial bones for different uses.